2022
DOI: 10.1038/s41467-022-34446-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of recent convergent transitions to social life in spiders

Abstract: The transition from solitary to social life is a major phenotypic innovation, but its genetic underpinnings are largely unknown. To identify genomic changes associated with this transition, we compare the genomes of 22 spider species representing eight recent and independent origins of sociality. Hundreds of genes tend to experience shifts in selection during the repeated transition to social life. These genes are associated with several key functions, such as neurogenesis, behavior, and metabolism, and includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 119 publications
(162 reference statements)
1
8
0
Order By: Relevance
“…Sociality has been estimated to have evolved independently about 18 times in spiders (Agnarsson et al., 2006) in various families such as Oxyopidae and Theridiidae. Recent studies have found convergent expressions of certain gene families in the social spider species (Tong et al., 2022). A stable placement of Eresidae is thus important to understand the evolution of social behaviour in spiders.…”
Section: Resultsmentioning
confidence: 99%
“…Sociality has been estimated to have evolved independently about 18 times in spiders (Agnarsson et al., 2006) in various families such as Oxyopidae and Theridiidae. Recent studies have found convergent expressions of certain gene families in the social spider species (Tong et al., 2022). A stable placement of Eresidae is thus important to understand the evolution of social behaviour in spiders.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon of convergent phenotypic evolution serves as a powerful framework to uncover the genetic underpinnings of adaptations to specific environments, as these phenotypic convergences commonly emerge due to parallel selective pressures. With the increasing accessibility of genomic datasets of diverse species, a growing body of recent studies on convergent phenotypic evolution has unveiled remarkable genomic similarities across distinct lineages [3][4][5][6][7][8][9]. Convergent phenotypic evolution is hypothesized to be associated with various genetic mechanisms of genomic convergences.…”
mentioning
confidence: 99%
“…For decades, studies on genomic convergences have primarily concentrated on the evolutionary dynamics of proteincoding genes [1][2][3][4][7][8][9]. By contrast, recent comparative genomic studies have begun to focus on the molecular evolution of non-coding regions across the genomes of diverse species, Types of genomic convergence.…”
mentioning
confidence: 99%
See 2 more Smart Citations